2004
DOI: 10.1152/ajprenal.00452.2003
|View full text |Cite
|
Sign up to set email alerts
|

AT1A-mediated activation of kidney JNK1 and SMAD2 in obstructive uropathy: preservation of kidney tissue mass using candesartan

Abstract: -Hamad. AT1A-mediated activation of kidney JNK1 and SMAD2 in obstructive uropathy: preservation of kidney tissue mass using candesartan. Am J Physiol Renal Physiol 287: F474 -F480, 2004. First published May 4, 2004 10.1152/ajprenal.00452.2003.-Literature suggests the involvement of the renin-angiotensin system and transforming growth factor (TGF)-␤ in the renal injury that follows chronic ureteric obstruction. SMAD proteins and the JNK1 cascade are essential components of TGF-␤ signaling machinery, and recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 44 publications
2
17
0
Order By: Relevance
“…AT 1 blockade downregulated Smad2 protein and activity and attenuated the chronic tubulointerstitial injury in obstructed kidneys. 9 These data indicate that Smad signaling could be a common mechanism of Ang II-mediated fibrosis in cardiovascular and renal diseases. The activation of the Smad signaling pathway causes nuclear translocation of Smads.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…AT 1 blockade downregulated Smad2 protein and activity and attenuated the chronic tubulointerstitial injury in obstructed kidneys. 9 These data indicate that Smad signaling could be a common mechanism of Ang II-mediated fibrosis in cardiovascular and renal diseases. The activation of the Smad signaling pathway causes nuclear translocation of Smads.…”
Section: Discussionmentioning
confidence: 89%
“…1,3,[5][6][7] AT 1 blockade diminishes Smad pathway activation in myocardial infarction in rats and in an experimental model of renal damage. 8,9 However, no studies have investigated whether Ang II activates the Smad signaling pathway in VSMCs and its potential role in vascular fibrosis.…”
mentioning
confidence: 99%
“…86 Administration of an angiotensin AT1 receptor inhibitor reduces c-Jun-N-terminal kinase (JNK1) activity and downregulates Smad2 activity in rats with UUO. 87 Interestingly, whereas HGF gene therapy alone reduces UUO-induced myofibroblast accumulation by 50%, combined HGF gene therapy and angiotensin AT1 receptor inhibition completely abolishes induction of α-smooth muscle actin and synergistically inhibits accumulation of collagen I. 88 The phenotypic transformation of fibroblasts to myofibroblasts involves upregulation of the early growth response gene 1 (Egr-1).…”
Section: Interstitial Fibrosismentioning
confidence: 99%
“…In addition, Moriyama et al (31) found that the ANG II receptor antagonist TCV-116 ameliorates the interstitial fibrosis and the progression of morphological changes in rat kidneys in response to complete UUO. Other studies have also shown that AT 1 -receptor blockade improved tubulointerstitial fibrosis in rats subjected to UUO (18,47).Inflammatory cell infiltration plays a key role in the onset and progression of renal injury in response to obstruction. Nuclear factor-B participates in the inflammatory response, regulating many proinflammatory genes.…”
mentioning
confidence: 90%